Novel Compound Heterozygous Variants of the ABCC8 Gene Warrant Identification of Pancreatic Histology in Infant with Diazoxide-unresponsive Congenital Hyperinsulinism - Rana Al Balwi; Dalal Bubshait; Raed Al Nefily; Omar Al Ghamdi (MDPI AG, 2021)
Congenital hyperinsulinism (CHI) is characterized by dysregulated insulin secretion, resulting in severe hypoglycemia. Mutations in the ABCC8 and KCNJ11 genes encoding KATP channels in beta cells of the pancreas are common among patients with CHI. Autosomal recessive CHI with diffuse involvement is the most common type of CHI among Saudi patients. It is relatively common for patients with autosomal recessive CHI to be medically unresponsive and undergo pancreatectomy. In this case report, we describe novel compound heterozygous variants in the ABCC8 gene in a Saudi infant that caused diazoxide-unresponsive CHI. The variants included a monoallelic paternally inherited variant that has been previously reported to cause a focal form of CHI and a maternally inherited variant of unknown significance (VUS). The severity of CHI in this patient was mild over the one-year follow-up period, with a near-optimal glycemic response on a low dose of octreotide. We suspected an atypical subtype of histological involvement in the patient. In this report, we highlight the phenotypic spectrum of novel compound heterozygous variants in a patient with CHI and consider that the report can help establish the pathogenicity of the VUS.